مبدأ الضرورة العسكرية في الفقه الإسلامي والقانون الدولي الإنساني. - مصطفاوي, بوبكر (University of Eloued جامعة الوادي, 2017)
هذا البحث يتناول مبدأ الضرورة العسكرية في الفقه الإسلامي والقانون الدولي الإنساني من خلال نصوص القرءان والسنة النبوية وعمل الصحابة – رضي الله عنهم – ونصوص اتفاقيات جنيف واتفاقيات لاهاي . لنتبين أن الضرورة العسكرية حالة ضمن نطاق النزاع المسلح تتطلب ظروف معينة تستلزم استخدام وسائل وأساليب قهرية وبأسرع وقت ممكن ووفق ضوابط ومقادير محددة والتي لا تسمح خلالها بتجاوز مقتضيات الإنسانية. فيتطرق البحث إلى مفهوم الضرورة العسكرية في الفقه الإسلامي والقانون الدولي الإنساني ومقدارها علما أنه لا يمكن إطلاق يد المقاتلين باسم الضرورة العسكرية . كذلك الضرورة العسكرية تحكمها ضوابظ تتمثل في مختلف النصوص المنظمة للنزاعات المسلحة في الشريعة الإسلامية أو القانون الدولي الإنساني , أيضا الضوابط الزمنية حيث الطابع المؤقت وسرعة التنفيذ , كذلك الضوابط المكانية وتشمل مصدر الضرر , ثم ضوابط الوسائل والأساليب ويندرج فيها الأسلحة ومدى خطورتها وأساليب القتال والتضييق كالحصار والتخويف , وأخيرا الضوابط الأخلاقية وتعني أساسا الوازع الديني والضمير العام للإنسانية حيث نشأ وتطور عبر العصور لتتشكل منه قواعد عرفية وأخلاقية تحكم النزاعات المسلحة وتسيطر على الرغبة في الانتقام. وفي ختام البحث خلصنا إلى نتائج أهمها: أن الحرب في الإسلام ضرورة عسكرية ردا للظلم والعدوان و للفتنة كما أن أعمال المسلم تعبدية , فلا يمكنه تجاوز الحدود ولو بدافع الضرورة العسكرية , كما أن الشريعة الإسلامية سباقة لإرساء قواعد النزاعات, وعلى المجتمع الدولي الاعتماد عليها في تطوير قواعد القانون الدولي الإنساني وهذا أهم مايوصي به هذا البحث إضافة إلى تحديد مفهوم الضرورة و حدودها ومقاديرها وحصر الحالات التي يمكن الاستناد عليها كضرورة العسكرية.This research deals with the principle of military necessity in Islamic jurisprudence and International humanitarian law through the texts of Quran and Sunnah and the work of the Companions - May Allah be pleased with them - and the texts of the Geneva Conventions and the Hague Conventions. Military necessity is a situation within the scope of the armed conflict that requires certain conditions that require the use of coercive means and methods as soon as possible and in accordance with specific controls and measures which do not allow breaking the requirements of humanity. The research deals with the concept of military necessity in Islamic jurisprudence and international humanitarian law and the extent that it is not possible to launch the hands of the fighters in the name of military necessity. The military necessity is also governed by the provisions of the various provisions governing armed conflicts in Islamic law or international humanitarian law, as well as temporal controls in terms of temporary nature and speed of implementation, as well as spatial controls, including the source of damage, controls of means and methods, weapons and their severity, methods of fighting and restrictions such as siege and intimidation. , And finally the ethical controls and means mainly the religious conscience and the general conscience of humanity where it grew up and evolved over the ages to form customary and ethical rules governing armed conflicts and control the desire for revenge. At the conclusion of the research, we concluded that the war in Islam is a military necessity in response to injustice, aggression and sedition, and that the actions of the Muslim are devotional and can not exceed the limits even if they are motivated by military necessity. The rules of international humanitarian law and this is the most important recommended by this research in addition to the definition of the concept of necessity and its limits and amounts and limit the cases that can be based on military necessity.
مذكرة ماستر تخصص شريعةوقانون
Keywords: : الضرورة العسكرية / الفقه الإسلامي / والقانون الدولي الإنساني / النزاع المسلح/ مقتضيات الانسانية/ اتفاقيات جنيف / اتفاقيات لاهاي: military necessity/ Islamic jurisprudence / International humanitarian law/ Armed conflict/ requirements of humanity/ Geneva Conventions / Hague Conventions.